(untitled) (Vietnam Journal of Community Medicine, 2026)
Objective: To determine the prevalence of dyslipidemia among young workers undergoing routine health check-ups at the University Medical Center Ho Chi Minh City. Participants and methods: A descriptive cross-sectional study was conducted on 358 individuals aged 18–40 years who attended routine health examinations at the University Medical Center Ho Chi Minh City and underwent a full lipid panel test including all four components. Results: The overall prevalence of dyslipidemia was 85.5%. Among the lipid abnormalities, elevated LDL-C was the most common, observed in 275 participants (76.8%). The prevalence of other lipid abnormalities was as follows: elevated triglycerides 60.5%, elevated total cholesterol 36.6%, and reduced HDL-C 21.5%. Conclusion: Dyslipidemia is highly prevalent among young workers, even in the absence of clinical symptoms.